Antibacterial therapy of nosocomial infections in neurosurgery in attitude of evidence-based medicine - Zozulya, Yu. A.; Tsymbalyuk, V. I.; Tkachik, I. P. (Ukrainian Neurosurgical Journal, 2008)
Currently available data on the diagnosis, and treatment of nosocomial infections at neurosurgical patients were discussed according to principles of evidence-based medicine. We represented data about main groups of nosocomial infections — postoperative pyoninflammatory complication, including the definition of neurosurgical site infection, pneumonia, intravascular device-related and urinary tract infection.